PENGARUH PERILAKU KEWIRAUSAHAAN TERHADAP KINERJA USAHA PETANI DI KALURAHAN NGARGOSARI - Dwi Budiyarti, Nanda; eko astuti, murwani (Universitas Sarjanawiyata Tamansiswa, 2024)
The objective of this study is to examine the impact of individual and environmental factors on the entrepreneurial behavior of farmers in the Ngargosari sub-district. Additionally, it aims to assess the influence of entrepreneurial behavior on the business performance of farmers, as well as the impact of environmental factors on their business performance. The research employed a quantitative approach utilizing Structural Equation Modeling (SEM) with SmartPLS 4.0 software as the analytical instrument. This study employed purposive sampling, encompassing a cohort of 63 respondents who are farmers residing in Ngargosari Village. The findings indicated that both individual variables and environemental factors has a significant effect on entrepreneurial behavior. Nevertheless, there is no empirical evidence to support the notion that entrepreneurial conduct has a substantial impact on business performance. The study revealed that environmental factors have a significant impact on the business performance of farmers in Ngargosari